A future for us: the gift of forgiveness - Grassi, Martín (Nuevo Pensamiento, 2023)
In this paper I intend to show that forgiveness is beyond any transactional or economic logic, and that it belongs to the realm of gifts. What is given in forgiveness is time, the possibility of a different and open future. Hope is, therefore, the soul of forgiveness. In fact, far from rejecting or forgetting a past offense, forgiveness is a different, and deferring memory; a memory that neither records nor replays past actions, but one that re-interprets the past from the promise of future, from the promissory capacity for building a community together